Ventricular activation time as a marker for complex ventricular arrhythmias, sudden cardiac death and ICD implantation in hypertrophic cardiomyopathy. (3rd October 2022) - Fragkiadakis, K; Marketou, M; Parthenakis, F; Kochiadakis, G
Abstract: Background: Identification of patients with hypertrophic cardiomyopathy (HCM) who are at high risk of sudden cardiac death (SCD) is essential, as life-threatening ventricular arrhythmias (VAs) can be effectively prevented with an implantable cardioverter defibrillator (ICD). Risk stratification using HCM Risk-SCD score is recommended in the 2014 ESC guidelines for the management of patients with HCM. However, the role of electrocardiogram (ECG) in risk stratification is less well established. Purpose: We investigated the association between the ventricular activation time (VAT), an ECG marker of the duration of ventricular depolarization, with the HCM Risk-SCD score, the presence of complex VAs, the implantation of an ICD and ICD-therapy for VAs. Methods: Patients with a history of HCM, documented by echocardiography, were studied. The 12-lead ECG and echocardiography were performed on the same day. On ECG, we evaluated the VAT in milliseconds, between the onset of the QRS complex to the peak of R wave on V5 or V6 precordial ECG leads. A careful personal and family history for unexplained syncope and SCD was obtained, respectively. The presence of non-sustained ventricular tachycardia (NSVT) and ICD therapy were assessed either with 48h ECG recording or ICD interrogation. HCM Risk-SCD score was calculated by the corresponding ESC online calculator. Statistical analysis was performed using the SPSS software. Results: Thirty-three patients with HCM were included (mean age 51±12 years, 78.8% male). According to the HCM Risk-SCD score, HCM patients were divided into three groups: low-risk (<4, 45.5%), intermediate-risk (4 to <6, 24.2%) and high-risk (>6, 30.3%) for SCD. Approximately half of the HCM patients had episodes of NSVT (48.5%) and an ICD (48.5%). Ventricular activation time was significantly prolonged in high-risk group compared either with intermediate-risk (74±24.5 vs 48.7±16.4, p=0.006) or low-risk (74±24.5 vs 44.3±12.6, p<0.001). HCM patients with NSVT had a significantly prolonged VAT compared with those without NSVT (62.19±25.2 vs 47.06±15.3, p=0.022). Moreover, HCM patients with an ICD had a higher VAT than those without an ICD (62.1±25.2 vs 47±15.3, p=0.003). VAT was also significantly prolonged in the group with appropriate ICD therapy for VAs compared with that without ICD therapy (82.8±22.1 vs 52.2±16.4, p=0.007). Finally, there was a significant positive correlation between VAT and NSVT (r=0.352, p=0.044), history of syncope (r=0.604, p<0.001), HCM risk-SCD score (r=0.493, p=0.004), ICD implantation (r=0.508, p=0.003) and ICD therapy (r=0.648, p=0.007) for VAs while there was not a correlation with the family history of SCD. Conclusion: Prolongation of VAT is associated with NSVT, HCM risk score for SCD, ICD implantation and ICD therapy for VAs in patients with HCM and it seems to be a novel, easy to measure, ECG marker for risk stratification. Funding Acknowledgement: Type of funding sources: None.